Risk Factors for Intravenous Acetaminophen-Induced Hypotension in Patients with Repeated Acetaminophen Administration - Kim, Sung-Ryeol; Son, Nak-Hoon; Park, Kyung Hee; Park, Jung-Won; Lee, Jae-Hyun (Yonsei medical journal, 2024)
Intravenous (IV) acetaminophen-induced hypotension is a clinically significant issue that remains difficult to predict. Therefore, this study aimed to identify the factors associated with hypotension in patients with repeated IV acetaminophen administration. This observational cohort study included patients who received IV acetaminophen in the critical care unit of the Yongin Severance Hospital in 2020. All IV acetaminophen administration records for each patient were reviewed, and the blood pressure records within 2 h after IV acetaminophen administration were examined. Changes in blood pressure within 2 h of IV acetaminophen administration were monitored to identify hypotension, defined as a systolic blood pressure <90 mm Hg, a decrease in systolic blood pressure by 30 mm Hg, or a decrease in mean arterial pressure by 15%. There were 1547 instances of IV acetaminophen administration among 398 patients. Of these, 416 instances (26.9%) resulted in hypotension among 204 patients (51.3%). A history of IV acetaminophen-induced hypotension did not predict subsequent hypotensive episodes, and there was no consistent tendency. The use of beta-blocker [odds ratio (OR)=1.50], gastrointestinal (GI) infection (OR=1.42), and septic shock (OR=1.68) were significant risk factors for IV acetaminophen-induced hypotension in multivariate analysis. In subgroup analysis of cases with beta-blocker, heart failure (OR=1.91), urinary tract infection (OR=2.16), GI infection (OR=1.83) were significant risk factors. Severe infections, heart failure, and the use of beta-blockers are associated with IV acetaminophen-induced hypotension. However, IV acetaminophen-induced hypotension is inconsistent and depends on the patient's condition.